An Investigation On Construction Sequence Of Irregular Single Layer Prism Tensegrity - Ong, Zhi Jia (Universiti Sains Malaysia, 2017)
Tensegrity structure is a self-balancing system where the continuous tensional cables and compressional struts are located among the cables where they could achieve rigidity through the application of pre-stressing. Tensegrity structure is a super sensitive structure and it will only achieve self-equilibrium when all the cables and struts are stressed. Construction of tensegrity structure is a very difficult process due to the highly unstable condition of tensegrity structure before pre-tension is applied. There is however limited information about actual construction sequences of tensegrity structure. In this study, a detailed study on practical construction sequences of tensegrity structure was carried out. Irregular single layer of prism tensegrity was the focus in this study. Method of force ratio calculation based on results of form-finding for construction purpose was determined by adopting elasticity and compatibility equation. Cables were designed to be shorter than length found from form-finding based on elongation calculated and forces introduced on cables were observed from elongation of cables. A practical sequence of construction of irregular single layer prism tensegrity was presented. A large scale tensegrity model was erected. A sequence whereby cables and struts were connected step-by-step and then pre-stressed to achieve the final shape was identified.